DEVELOPING QUIZIZZ-BASED MATHEMATICS LEARNING MEDIA ON EXPONENTS TO IMPROVE HIGH SCHOOL STUDENTS’ LEARNING OUTCOMES - Melda Aini Cahyani; Putri Sukma Dewi (Universitas Muhammadiyah Metro, 2026)
This study aims to develop Quizizz-based mathematics learning media on exponents to improve high school students' learning outcomes. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages (Sugiyono, 2023). Data were collected through expert validation (media and material experts) and learning outcome tests in the form of pretests and posttests. The research subjects were 35 tenth-grade students of SMAN 16 Bandar Lampung in the 2025/2026 academic year, selected using a random sampling technique. The results showed that the average score increased from 59.14 in the pretest to 87.29 in the posttest. Furthermore, the statistical test using the Wilcoxon Signed-Rank Test indicated a significant difference between pretest and posttest results (p < 0.05). This finding demonstrates that the developed Quizizz-based learning media is effective in improving students’ learning outcomes. Penelitian ini bertujuan untuk mengembangkan media pembelajaran matematika berbasis Quizizz pada eksponen untuk meningkatkan hasil belajar siswa SMA. Penelitian ini menggunakan metode Penelitian dan Pengembangan (R&D) dengan model ADDIE, yang terdiri dari tahapan analisis, desain, pengembangan, implementasi, dan evaluasi (Sugiyono, 2023). Data dikumpulkan melalui validasi ahli (ahli media dan materi) dan tes hasil belajar berupa pretest dan posttest. Subjek penelitian adalah 35 siswa kelas 10 SMAN 16 Bandar Lampung tahun ajaran 2025/2026, yang dipilih menggunakan teknik random sampling. Hasil penelitian menunjukkan bahwa nilai rata-rata meningkat dari 59,14 pada pretest menjadi 87,29 pada posttest. Lebih lanjut, uji statistik menggunakan Uji Peringkat Bertanda Wilcoxon menunjukkan perbedaan signifikan antara hasil pretest dan posttest (p < 0,05). Temuan ini menunjukkan bahwa media pembelajaran berbasis Quizizz yang dikembangkan efektif dalam meningkatkan hasil belajar siswa.